E-002 Initial experience with the Penumbra stroke system for recanalization of large vessel occlusions in acute ischemic stroke. (16th November 2010) - Menon, B; Hill, M; Eesa, M; Modi, J; Bhatia, R; Wong, J; Hudon, M; Morrish, W; Demchuk, A; Goyal, M
Abstract : Background: The Penumbra system is a newly approved mechanical device for the treatment of acute stroke designed for better and faster recanalization. We describe our initial experience with the use of this device. Methods: We studied 27 consecutive patients with acute ischemic stroke from January 2009 to October 2009 at our stroke centre. The primary outcome was the degree of reperfusion (TIMI grade 2/3) at end of the procedure. Secondary end points were the proportion of patients who achieved a modified Rankin Scale (mRS) ≤2 at 3 months, all cause mortality and intracerebral hemorrhage (ICH) on non-contrast CT at 24 h. Procedural complications such as vascular perforations, vasospasm, dissection, distal embolization and groin complications were recorded. Results: 27 patients (13 men, mean age 61 years) were treated during the period January–October 2009. Median National Institutes of Health Stroke Scale on admission was 18 (range 3–32), median Alberta Stroke Program Early CT Score on non-contrast CT at admission was 8 (range 5–10) and median onset to intra-arterial treatment time was 192 min. 22 (81%) patients had anterior circulation strokes. 17 (63%) had intravenous tissue plasminogen activator initiated prior to angiography. 85% (23/27) patients achieved TIMI 2/3 grade reperfusion at completion of the procedure. 48% (13/27) patients had mRS ≤2 at the 3 month follow-up. Procedural complications included vasospasm (1/27), distal emboli (13/27) and ICH (seven HI1, one PH1 and one PH2). All cause mortality was 19% (5/27). Conclusions: High reperfusion rates and good clinical outcomes are achievable with the Penumbra system. Complication rates are comparable with the previously published literature.